Analisis Daya Saing Gula Merah Tebu Di Kabupaten Aceh Tengah - Bagio Bagio; Romano Romano; Yusya Abubakar (Jurnal Agrisep, 2016)
Agricultural products in form of raw materials have low economic value. Thus the development of agriculture contibute a few at people's income. Its functions in people's income could be seen on these factors namely, input and output transfer, tchnology, and the added value of the final agricultural products. The gtreater the added value of product the greater it gives the contribution on increasing people's income. This research aimed at indentification of analyze the competitiveness of brown palm sugar in Aceh Tengah. The method used is suvey in which data primer and secunder related to competitiveness of brown plam sugar in Aceh tengah is used properly. Anlysis model that was used Domestic Resource Cost. The result of the research cane farming in Aceh Tengah has its comparative advantage in which its domestic resource cost coefficients around 0,496 to 0,596. After a sensitivity analysis, the value of domestic resource cost coefficients still less than 1, the ecomonic activity has comparative advantage. Sensitivity analysis showed that cane farming in Aceh Tengah has its comparative advantage in which its domestic resource cost coefficients 1. It meant that an ecomonic activity of brown cane sugar were economicly efficient in domestic resource utilization, or it could be said that an economic activity has comparative advantage.